The Influence of the Human Resources (HR) Recruitment System on Employee Performance at PT. Bank Rakyat Indonesia (PERSERO) Tbk Pinrang Branch - Febi Febrianti; Moh. Aris Pasigai; M.Hidayat (International Journal of Economic Research and Financial Accounting, 2024)
This research aims to determine the influence of the recruitment system (HR) on employee performance at PT. Bank Rakyat Indonesia Pinrang Branch. The population in this research is all employees of PT. Bank Rakyat Indonesia with the number of respondents. This type of research used is quantitative descriptive. The data sources used are primary and secondary data where the primary data comes from observations and questionnaires. Meanwhile, secondary data is obtained from documentation. The data analysis technique used is Simple Regression Analysis using statistical calculations via the Statistical Package for the Social Science (SPSS) version 26 application. Results of research regarding the Influence of the Human Resources (HR) Recruitment System on Employee Performance at PT. Bank Rakyat Indonesia (Persero) Tbk Pinrang Branch found that the recruitment system variable had a positive influence with tcount (15.160) > ttable (0.214) positive and significant results, the Recruitment System variable obtained a tcount of 15.160 and a ttable of 0.214.